(untitled) (National Administration Journal, 2023)
Work commitment is an observable process in times of crisis or job stability. Given that the structure of work commitment is influenced by various dimensions observed during the pandemic, the aim of this study was to demonstrate its structure of mediating relationships. For this purpose, an exploratory, cross-sectional, and psychometric study was conducted with a sample of 100 students. Once the factorial structure was explored, a second study was carried out to confirm the structure using another sample of students. The selection criteria were related to inclusion in professional internships and community service in community centers. The results indicate that the fit and residual parameters suggest the non-rejection of the null hypothesis regarding significant differences between the theoretical structure and empirical observations. In relation to paradigms, it is assumed that extending the model would be relevant in order to predict job performance.